Flexible majority rules for cryptocurrency issuance - Hans Gersbach (ETH Zurich, CER-ETH - Center of Economic Research, 2019)
We suggest that flexible majority rules for currency issuance decisions foster the stability of a cryptocurrency. With flexible majority rules, the voteshare needed to approve a particular currency issuance growth is increasing with this growth rate. By choosing suitable parameters for these flexible majority rules, we show that optimal growth rates can be achieved in simple settings. Moreover, with flexible majority rules, changes in the composition of growth-friendly and growth-adverse agents only have a comparatively moderate impact on growth rates, and extreme growth rates are avoided. Finally, we show that optimal money growth rates are realized if agents entering financial contracts anticipate ensuing inflation rates determined by these flexible majority rules.
Keywords: D72; E31; E42; E52; E58; 330; Digital currency; central bank; voting; majority rule; flexible majority rules